2009
DOI: 10.1055/s-0029-1234043
|View full text |Cite
|
Sign up to set email alerts
|

Glucose, Metformin, and AICAR Regulate the Expression of G Protein-coupled Receptor Members in INS-1 β Cell

Abstract: Glucagon-like peptide-1 receptor (GLP-1R), glucose-dependent insulinotropic polypeptide receptor (GIPR), and G protein-coupled receptor 40 (GPR40) are members of G protein-coupled receptors (GPCR) family. They are abundantly expressed in islet beta cells, and mediate effects of incretins and fatty acids in beta cells. Glucose and 5-AMP-activated protein kinase (AMPK) are known to be involved in the regulation of beta cell function. Metformin and the potential therapeutic drug for type 2 diabetes, 5-amino-4-imi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
1
28
0
2
Order By: Relevance
“…In the second section of our study, we demonstrated that subchronic treatment of mice with metformin leads to enhanced expression of the Glp1r and Gipr genes in murine islets. Pan and colleagues indirectly implicated a role for AMPK in the actions of metformin on islet gene expression via their demonstration that AICAR mimicked the actions of metformin on Glp1r and Gipr mRNA transcripts in INS-1 cells [26]. In contrast, our data demonstrate that AICAR downregulates Glp1r and Gipr mRNA transcripts in INS-1 832/3 beta cells.…”
Section: Glp1r Glp1rmentioning
confidence: 46%
See 1 more Smart Citation
“…In the second section of our study, we demonstrated that subchronic treatment of mice with metformin leads to enhanced expression of the Glp1r and Gipr genes in murine islets. Pan and colleagues indirectly implicated a role for AMPK in the actions of metformin on islet gene expression via their demonstration that AICAR mimicked the actions of metformin on Glp1r and Gipr mRNA transcripts in INS-1 cells [26]. In contrast, our data demonstrate that AICAR downregulates Glp1r and Gipr mRNA transcripts in INS-1 832/3 beta cells.…”
Section: Glp1r Glp1rmentioning
confidence: 46%
“…The effect of metformin on islet incretin receptor expression As metformin upregulates the expression of incretin receptors in an islet cell line in vitro [26], we assessed whether metformin modulates pancreatic or islet incretin receptor expression in murine islets. Metformin-treated mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the uterine PPARg pathway regulates implantation in mice by modulating the 12/15 LOX system (26). These findings, together with the fact that metformin and the PPAR system have been related in a synergistic action (27,28), led us to study the expression of PPARg, 12-LOX, and 15-LOX in uterine tissue from hyperandrogenized mice and their relationship with the metformin treatment.…”
mentioning
confidence: 99%
“…We used an AICAR [19] and inhibitor (compound C) [20] to determine the effects of AMPK on the mRNA expression of ubiquitin E3 ligases. When AICAR activates AMPK, we show that the mRNA expression of ubiquitin E3 ligases is enhanced, which is consistent with a previous study [6].…”
Section: Discussionmentioning
confidence: 99%